The role of class I HLH genes in neural development-have they been overlooked? - Heng, J.I.T.; Tang, S.S. (BioEssays, 2003)
Helix-loop-helix (HLH) genes encode for transcription factors affecting a whole variety of developmental programs, including neurogenesis. At least seven functional classes (denoted I to VII) of HLH genes exist, (1) with subclass members exhibiting homo- and heterodimerisation for proper DNA binding and transcriptional regulation of downstream target genes. In the developing nervous system, members of class II, V and VI have been most extensively studied concerning their roles in neural programming. In contrast, the function of class I proteins (such as E12 and E47) is poorly defined and the orthodox view relegates them to general dimerisation duties that are necessary for the activity of the other classes. However, closer scrutiny of the spatiotemporal expression patterns of class I factors, combined with recent biochemical evidence, would suggest that class I proteins possess specific functions during early neural differentiation. This essay supports this possibility, in addition to putting forward the hypothesis that, outside their general dimerisation activity, class I genes have independent roles in regulating neurogenesis.